The Effect of Isolated Finger Stiffness on Adjacent Digit Function. (May 2018) - Baaqeel, Rasha; Wu, Kitty; Chinchalkar, Shrikant J.; Ross, Douglas C.
Background: Isolated stiffness in a single finger can affect the function of adjacent digits and decrease overall hand function due to the quadriga phenomenon. This study objectively quantifies the dysfunctional impact of each individual stiff finger upon the remaining digits.Methods: Twenty-five individuals (10 men and 15 women) with a mean age of 31 years (range, 18-58 years) without any upper limb pathology, neuropathy, or systemic illness were recruited. Volar-based finger splints were used to hold individual digits of the dominant hand (24 right and 1 left) sequentially in full extension at the metacarpophalangeal (MCP), proximal interphalangeal (PIP), and distal interphalangeal (DIP) joints. Motion of the remaining 3 nonsplinted digits was assessed using a finger goniometer and linear scale to measure the total active range of motion (TAM) and fingertip-to-distal palmar crease (DPC) distance. TAM before and after splinting for each digit was compared using 1-way analysis of variance (ANOVA).Results: Splinting of any individual finger resulted in a significant reduction in the TAM of all adjacent fingers, regardless of which finger was splinted ( P < .001). Digits immediately adjacent to the splinted finger were more heavily impacted compared with nonadjacent digits. Splinting of the ring finger produced the greatest detriment, with a 26% to 47% reduction in the TAM and a DPC distance greater than 40 mm in a third of participants. The index finger caused the least disturbance to remaining digital motion.Conclusions: Isolated finger stiffness causes a variable degree of dysfunction on adjacent normal digits. This emphasizes the need for a focused and proactive approach to restore full active motion following isolated finger injuries to prevent persistent functional sequelae of the hand.